2016
DOI: 10.1021/acs.jnatprod.6b00575
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Lanostanoids from Poria cocos

Abstract: Six new and 16 known lanostanoids were isolated from the sclerotia of Poria cocos. The structures of the new isolates were elucidated to be 16α-hydroxy-3-oxo-24-methyllanosta-5,7,9(11),24(31)-tetraen-21-oic acid (1), 3β,16α,29-trihydroxy-24-methyllanosta-7,9(11),24(31)-trien-21-oic acid (2), 3β,16α,30-trihydroxy-24-methyllanosta-7,9(11),24(31)-trien-21-oic acid (3), 3β-acetoxy-16α,24β-dihydroxylanosta-7,9(11),25-trien-21-oic acid (4), 3β,16α-dihydroxy-7-oxo-24-methyllanosta-8,24(31)-dien-21-oic acid (5), and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Compounds are placed into a chemical space based on their properties, which can be calculated from simplified molecular input line entry specification (SMILES) structure data, followed by execution of score prediction in ChemGPS-NP. The system provides a bioinformatics tool for plotting and navigating biologically relevant chemical spaces (Larsson et al, 2007; Lai et al, 2016). It can further serve as a tool for discussing the structure-activity relationships as well as to predict possible bioactivities for specific groups of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds are placed into a chemical space based on their properties, which can be calculated from simplified molecular input line entry specification (SMILES) structure data, followed by execution of score prediction in ChemGPS-NP. The system provides a bioinformatics tool for plotting and navigating biologically relevant chemical spaces (Larsson et al, 2007; Lai et al, 2016). It can further serve as a tool for discussing the structure-activity relationships as well as to predict possible bioactivities for specific groups of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…P. cocos is an edible and medicinal mushroom of the Polyporaceae family, which is widely used as nutritious food, dietary supplements and traditional medicine in Asia (34,35). Increasing experimental evidence suggests that triterpenes isolated from P. cocos exert direct anticancer effects through a variety of mechanisms, including the inhibition of cell proliferation, induction of apoptosis and suppression of invasive behavior (36)(37)(38)(39)(40). In our previous study, PTE, PA, DPA and PPAC were found to inhibit the growth of pancreatic cancer cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…ChemGPS-NP, a PCA (Principle Component Analysis)-based model applied to natural products, was first developed by the Backlund group in 2007 [ 11 ], and an entire online analysis system that provides the eight principal components (PCs) was further established by the same group in 2009 [ 12 ]. In the last few years, this computational tool has been employed to analyze structure-activity relationships (SAR) [ 13 , 14 ] and to further investigate promising pharmacological targets, guiding natural product drug discovery [ 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%